Childhood and politics - Jens Qvortrup (Educare)
Our culture’s attitudes towards children are ambiguous – as found also in the relationship between children and politics. The protective mood that has befallen children over the last two centuries entails their separations from adults – and from the serious business of economics and politics. How do we deal with the dilemma, which as a consequence makes it difficult to have a discourse about children and politics? This article nevertheless makes some reflections over the theme and suggests that one can, as far as politics is concerned, in principle talk about (a) children as subjects, (b) children/childhood as a non-targeted object (i.e. in terms of structural forces’ impact), (c) children/childhood as targeted objects (political initiatives having children in mind), and finally as (d) instrumentalised objects. The thorny question raised in each case is to which extent children are beneficiaries or if that is the case primarily as a side effect of gains to adults/adult society. Would public investments in children have been made to the current extent, if expectations of a surplus return were not an option?